2009
DOI: 10.1109/tvcg.2009.116
|View full text |Cite
|
Sign up to set email alerts
|

ABySS-Explorer: Visualizing Genome Sequence Assemblies

Abstract: Fig. 1. ABySS-Explorer employs a novel graph representation enabling biologists to examine the global structure of a genome sequence assembly.Abstract-One bottleneck in large-scale genome sequencing projects is reconstructing the full genome sequence from the short subsequences produced by current technologies. The final stages of the genome assembly process inevitably require manual inspection of data inconsistencies and could be greatly aided by visualization. This paper presents our design decisions in tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 21 publications
(26 reference statements)
2
40
0
Order By: Relevance
“…Our follow-up study, furthermore, showed C b providing no significant improvement over C [14]. Nielsen et al [20] note that they were inspired by our initial-study results. For their ABySSExplorer they use tapering to depict the orientation of "contigs," i.e., genome assemblies consisting of long contiguous sequences.…”
Section: Static Directed-edge Representationsmentioning
confidence: 53%
“…Our follow-up study, furthermore, showed C b providing no significant improvement over C [14]. Nielsen et al [20] note that they were inspired by our initial-study results. For their ABySSExplorer they use tapering to depict the orientation of "contigs," i.e., genome assemblies consisting of long contiguous sequences.…”
Section: Static Directed-edge Representationsmentioning
confidence: 53%
“…Abstraction should happen very early in the discovery stage and should frequently be validated by checking back with the expert to ensure correctness. One design study where we put significant effort into articulating the abstractions clearly and concisely was MizBee [45]; ABySS-Explorer is an excellent example from other authors [56].…”
Section: Discover : Problem Characterization and Abstractionmentioning
confidence: 99%
“…A task abstraction will either be a good or a bad reflection of the actual domain, while a data abstraction proposed by the researcher will be appropriate or inappropriate for the specific problem at hand. An interesting example is the ABySS-Explorer project [56] where the computational algorithms that assemble a genome from sequence data rely on a graph with unique sequence strands represented as nodes and overlapping strands as edges. The visualization researchers observed, however, that the experts often used a dual representation (swapping nodes and edges) when sketching their ideas on paper, and found that building their visualization tool around this swapped representation allowed the domain scientists to reason about the output of the algorithms very effectively.…”
Section: Design: Data Abstraction Visual Encoding and Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, more specifically, the use of circular arcs for edges has received attention (e.g., [7]), in particular the creation of Lombardi drawings [6]. The use of regular sinusoid curves to indicate relative length was recently introduced by Nielsen et al [14] for the visualization of connectivity graphs in genome sequencing. Lastly we note the topic of map labeling, where a suitable position of each label must be found among a set of candidate positions (see [20] for a survey).…”
Section: Related Workmentioning
confidence: 99%